Rancang Bangun Sistem Informasi Inventori (Studi Kasus UD Sejahtera) - Michael Christian Chandra; Trianggoro Wiradinata (Jurnal Informatika dan Sistem Informasi, 2015)
Inventory is known to be one of the most an important factor to ensure smooth sales process. Hence the company must ensure sufficient supplies so that the sales process is not hampered. A good inventory management is needed in order to ensure the sufficiency of inventory item. Common problems found in the inventory management are (1) delays, (2) limited stock, (3) and unfavorable stock items. Through seamless integration of inventory management systems, procurement, and sales processing, company can monitor the condition of the inventory, distribution of goods, monitoring the position of the goods with no difficulties. This study took U.D. Sejahtera as implementation object which previously had inventory management problem. After implementing the inventory management system, they managed to streamline their procurement, inventory and sales process effectively and efficiently. The impact of the implementation were owner and managers able to focus on business expansion rather than trapped in daily routine problems.